2017
DOI: 10.1016/j.rmed.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic involvement in IgG4-related disease in a UK-based patient cohort

Abstract: IgG4-related disease (IgG4-RD) is a multi-system fibro-inflammatory disorder with classical histopathological findings, often in the context of elevated serum IgG4 levels. The thoracic manifestations of IgG4-RD are numerous and can mimic several common and better known conditions. The objective of this study was to outline the frequency and nature of thoracic involvement in a prospective cohort of IgG4-RD patients who met defined diagnostic criteria. Over 40% of IgG4-RD patients had clinicoradiological and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
6

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 19 publications
0
40
0
6
Order By: Relevance
“…Patients with IgG4-RD are referred from local, regional, and national hospitals, and video-linked multidisciplinary team meetings are held every 6 weeks between the London and Oxford groups. Patients with autoimmune pancreatitis, IgG4-sclerosing cholangitis, IgG4-related lung disease, and 1 patient with IgG4-RPF in this cohort have previously been reported 15, 16, 17…”
Section: Methodsmentioning
confidence: 68%
“…Patients with IgG4-RD are referred from local, regional, and national hospitals, and video-linked multidisciplinary team meetings are held every 6 weeks between the London and Oxford groups. Patients with autoimmune pancreatitis, IgG4-sclerosing cholangitis, IgG4-related lung disease, and 1 patient with IgG4-RPF in this cohort have previously been reported 15, 16, 17…”
Section: Methodsmentioning
confidence: 68%
“…Since then, it has been recognized as an immune-mediated condition involving several organs, particularly exocrine organs such as the pancreas, salivary glands, and biliary tract [1]. Several studies have reported that intrathoracic involvement may be seen in about 10 to 50% [2,4,5], which commonly includes interstitial lung disease, inflammatory pseudotumors, fibrosing mediastinitis, and lymphadenopathy. The formation of a mass in the anterior mediastinum, mimicking an anterior mediastinal tumor, is very rare.…”
Section: Discussionmentioning
confidence: 99%
“…IgG4-related disease (IgG4-RD) is a systemic disease characterized by an elevated serum IgG4 level and lymphoplasmacytic infiltration of multiple organs, such as the pancreas, salivary glands, and biliary tract [1]. In the respiratory system, it commonly presents as pulmonary nodules, lymphadenopathy, or sclerosing mediastinitis [2]. We present a case of IgG4-related disease forming a mass in the anterior mediastinum.…”
Section: Introductionmentioning
confidence: 99%
“…30 These reports, however, do not include mediastinal and airway manifestations and thereby underestimate the frequency of thoracic involvement which may be nearly one-half of patients. 5,15 Most cases of thoracic involvement with IgG4-RD are found incidentally during the workup of extrathoracic lesions. As such, patients with thoracic IgG4-RD may not manifest overt respiratory symptoms, for example, mediastinal lymphadenopathy.…”
Section: Thoracic Manifestations Of Igg4-rdmentioning
confidence: 99%
“…Intrathoracic lymphadenopathy involving the mediastinum and hilum has been reported to be the most common form of thoracic involvement in IgG4-RD in some studies but not in others. 5,15 In these cases of IgG4-RD-related intrathoracic lymphadenopathy, the diagnosis is often based on imaging without histopathologic confirmation in the presence of documented IgG4-RD elsewhere in the body. Mediastinal involvement in IgG4-RD can also manifest mediastinal mass or fibrosing mediastinitis.…”
Section: Mediastinal Diseasementioning
confidence: 99%